(untitled) (Research, Society and Development, 2020)
The study aims to verify the main strengths and weaknesses existing in the implementation of reception with risk classification in obstetric emergency. It is an integrative review built in March 2020 through searches in the Virtual Health Library, Google Scholar and Medical Literature Analysis and Retrieval System Online, with the health descriptor “host” and the keywords irregular: “risk classification ”And“ obstetric emergency ”. Documents in full article format, written in Portuguese and / or English, published between 2015-2020 were included and revision surveys were excluded, which did not have free access, in duplicate and in their title and / or abstract did not include the content under discussion, thus resulting in a total of 9 documents selected for the construction of this review. The qualification of assistance and improvement of the flow of care are listed as the main potentialities associated with the implementation of the reception policy with risk classification and the lack of permanent education, agreement with primary care and material resources as the main weaknesses. In view of this scenario, it is necessary that health services strengthen permanent education, professionals seek to empower themselves with the theme and that primary care strengthens their actions to improve the care provided to pregnant women and mothers of the Unified Health System.